Interaction of Cultural Media Composition with EM4 Dosage on Population Growth, Biomass and Nutritional Content Silk Worm (Tubifex SP) - Murni Murni; Herliwati Herliwati; Noor Arida Fauzana (Publikasi Indonesia, 2022)
Culture media as a place for the maintenance of silk worms greatly affects the growth and nutritional content of silk worms. The purpose of this study was to analyze the interaction effect of the composition of culture media with a dose of EM4 on population growth, biomass and nutritional content of silk worms (Tubifex sp). This study used a completely randomized factorial design with 9 treatments and 3 replications each. Treatment D1M1, treatment D1M2, treatment D1M3, treatment D2M1, treatment D2M2, treatment D2M3, treatment D3M1, treatment D3M2 and treatment D3M3. Each treatment was kept in 27 trays. The resu its showed that the composition of the media material and the dose of EM4 had a very significant effect (P< 0.05) on population growth and biomass and nutritional content of silk worms. The highest average population and biomass growth was obtained in the D2M2 treatment, which was 27482.9 ind/m2 and 8.52 grams, and the best nutrient content was in the D3M3 treatment with a protein content of 50.88. Based on the results of the study, it can be concluded that the combination of media materials with a percentage of 50% azolla pinnata and 50% chicken manure can increase the population, biomass and nutritional content of silk worms.